PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN BRAND IMAGE TERHADAP KEPUASAN PELANGGAN PT ERHA DERMACENTER PONDOK INDAH JAKARTA SELATAN - Lucy Nancy Simatupang; Nurul Maulida (Jurnal Manajemen, 2019)
This study aimed to determine the effect of Product Quality, Service Quality, and Brand Image on Customer Satisfaction. The method used in this study is a quantitative method and the assessment of the results of this study is based on respondents' answers using a Likert Scale. The population in this study were all customers who made product purchases at Erha Derma Center Pondok Indah, South Jakarta, more than 2 times the purchase and become customers and the sample in this study amounted to 71 respondents. The method of analysis in this study uses Instrument Test (Validity and Reliability), Data Normality Analysis, Assumption Test (Normality, Multicolonity, Heteroscedaticity, Autocorrelation), Correlation Coefficient Test, Multiple Linear Regression Test, T Test, F Test, and Determination R2. From the results of the F test (simultaneously),the results have been obtained that the Product Quality variable (X1), Service Quality (X2), and Brand Image (X3) have an influence and significant on Customer Satisfaction (Y), while the t test results (Partially ) found the variable Brand Image (X3) has no effect and is not significant to Customer Satisfaction (Y), but vice versa with variables (X1) and (X2) to (Y).